Development of Hybrid IgG-Aptamer Sandwich Immunoassay Platform for Aflatoxin B1 Detection and Its Evaluation Onto Various Field Samples - Aswani Kumar, Y. V. V.; Renuka, R. M.; Achuth, Jayakrishnan; Venkataramana, M.; Ushakiranmayi, M.; Sudhakar, P. (Frontiers in Pharmacology, 2018)
The present study was aimed to develop a novel antibody-aptamer based hybrid detection strategy for specific and sensitive detection of aflatoxin B1 (AFB1) from contaminated food grains. The study comprises generation of ssDNA aptamers and anti-AFB1 IgG antibodies against the AFB1 toxin. The generated bio-probes (aptamers and antibodies) were further characterized for their specificity and sensitivity using indirect ELISA. The generated aptamers namely AFB1a and AFB1b showed prominent reactivity and selectivity against the AFB1 toxin. These aptamers were further characterized for their secondary structures and dG values were determined as -4.6 and -2.75 Kcal/mol, respectively. The detection limit (LOD) of AFB1a and anti-AFB1 IgG antibodies was determined as 5 and 10 ng/mL, respectively. The characterized aptamers and antibodies against AFB1 were used to develop the sandwich immunoassay. Anti AFB1 IgG antibody was used as a capturing antibody whereas anti-AFB1a aptamer was used as its revealing partner in the assay. The limit of detection of the immunoassay was determined to be 5ng of AFB1 standard toxin and showed no cross-reactivity with closely related mycotoxins. To assess the reliability of the developed method, several field samples contaminated with aflatoxin B1 was included in the study and results were validated with commercial AFB1-ELISA Kit. Additionally, the spiking studies were also carried out to demonstrate the consistency and dependability of the developed hybrid sandwich immunoassay wherein the toxins recovered were found to be ranging between 73% to 98.80% with the limit of detection at 5ng. In conclusion, the developed method may find the better utility in routine food testing laboratories for assessment of AFB1.